Cast-Saw Injuries: Assessing Blade-to-Skin Contact During Cast Removal: Does Experience or Education Matter?. Issue 1 (February 2014) - Monroe, Kirstin C.; Sund, Sarah A.; Nemeth, Blaise A.; Noonan, Kenneth J.; Halanski, Matthew A.
Abstract: Background: Cast-saw injuries are sustained during cast removal or splitting of a cast when a hot cast-saw blade touches the patient's skin inadvertently during cast removal. Other studies have evaluated risk factors associated with saw-blade temperature, however, none have documented the number and duration of blade-to-skin contacts during cast removal.Methods: Using a pediatric long-arm model capable of detecting cast-saw blade contact, we tested the ability of health care providers to apply and remove casts before and after a brief education module. The total number and duration of "touches" between the saw and the model's "skin" were recorded. Correlations between user "touches, " and experience and comparisons between pre- and post-education "touches" were performed.Results: Of the 18 study participants, 16 touched the model surface with the cast saw; 7 of the 18 participants maintained blade contact with the skin for > 1 second 22 times during the testing process. Participants with less experience averaged 20 (± 16) touches, whereas more experienced participants averaged 24 (± 19) touches ( P = 0.7). Average number of touches was similar—before 22 (± 20) and after 25 (± 22); P = 0.5—participants completed an education module. No correlation between experience or participation in the education program was found with decreased number of blade-to-skin touches.Conclusion: Nearly all clinicians inadvertently contacted the underlying skin with the cast-saw blade. In our limited sample size, experience and education did not prevent this; therefore, minimizing time of contact and blade temperature may be more important factors in minimizing cast-saw injuries.